Climate change and its impact on human habitat in Darbandikhan district - محمد‌امین, آ.م.د. هاوري ياسين محمد‌امین; احمد, آ.م.د. شؤخان محمد احمد (Sulaimani Journal for Humanities, 2025)
Climatic elements are considered one of the most important factors in the well-being of human activities. If the climatic conditions are more or less than their normal state, it affects human activities, causes boredom, and affects health. This is called the phenomenon of climate fluctuation. The aim of this study is to demonstrate the impact of climate change on the environment of human shelters in the Darbandikhan region. This study describes the climate of the study area, rainfall variation, Temperature Humidity Index (THI), and Wind Chill Index (Ko) during twenty-one years (2000 - 2020). The highest amount of precipitation occurred, and the highest amount of precipitation fell during the monitoring period was in the year (2018-2019), when the total annual precipitation amounted to 1339.2 mm, and the lowest amount of precipitation was in the year (2007-2008), when the amount of rain decreased to (206.2 mm). As for the average annual deviation, the deviation appears in the negative direction and there is less rainfall in a total of (11) years compared to (10) years of positive deviation. According to the temperature and humidity index (THI) and the temperature and wind index (Ko) we discover that the fluctuations that occurred in the region’s climate affected the level of human comfort during the period (21) years, but the highest rate of fluctuations occurred in the months of spring and fall.
Keywords: Climate; meteorology; temperature and humidity index